ChemInform Abstract: The Cross‐Selective Titanium(III)‐Catalyzed Acyloin Reaction. Issue 43 (21st October 2014) - Feurer, Markus; Frey, Georg; Luu, Hieu‐Trinh; Kratzert, Daniel; Streuff, Jan
Abstract A Ti(III)‐catalyzed intermolecular reductive coupling of ketones (I) and (IV) or imine (VI) with nitriles (II) is described, which gives direct access to α‐hydroxylated and α‐aminated ketones, respectively.